Single and two stage diffusion process by different chemicals combinations for treatment of rubber wood - Jose V T; Jayarathnam K; Nehru C R; Rajalakshmy V K (Indian Journal of Natural Rubber Research, 1995)
Treatment of rubber wood by diffusion process using sodium pentachlorophenate in combination with either zinc sulphate was found to be very effective for the preservation of both fungal and insect attack. Zinc sulphate or copper sulphate can be considered as a substitute for borax, boric acid combination against insect attack in the preservative treatment of rubber wood. It was found that single stage diffusion process after two consecutive dippings in sodium pentachlorophenate and in either zinc sulphate or copper sulphate is equally effective as two stage diffusion process, first with sodium pentachlorophenate and then with either zinc sulphate or copper sulphate.
Keywords: Diffusion process; Insect borer; Rubberwood; Sapstain fungus; Wood preservation